Attrition of Thoroughbred and Standardbred racehorses at New York Racetracks due to exercise and non-exercise related fatalities during the 2016 - 2019 racing seasons - Palmer, S.; Morales Gomez, A. M.; Mohammed, H. O. (Journal of Equine Veterinary Science, 2021)
A longitudinal retrospective study was carried out to investigate the attrition of Thoroughbred (TB) and Standardbred (SB) horses racing at New York racetracks during the 2016 to 2019 seasons. The data were collected from the New York State Gaming Commission (NYSGC) Equine Breakdown, Death, Injury and Incident (EBDII), The Jockey Club InCompass Solutions, and The United States Trotting Association Pathway databases. Survival analysis was used to compare the predisposing factors by breed of the horse. The study included 431 horses (360 TB and 71 SB). There was a significant difference between the average incidence of attrition events per start for TB (0.304) and SB (0.035) horses. There was a significant difference in the median age to attrition between TB (4.2 years) and SB (7.5 years) horses. There was also a significant difference between the average number of starts to attrition for TB (13.6) and SB (125.5) horses. Among the causes of attrition events in the two breeds musculoskeletal injuries and medical conditions were significantly higher among TB horses, while sudden death was significantly higher among SB horses. The multivariate analysis showed that the hazard of attrition was affected by the age of the horse, age at first start, whether the horse was intact male, type of activity (racing training or other) and the breed of the horse. SB horses were less likely to experience attrition events in comparison to TB horses.